Diagnosis of thyroid disease using artificial neural network methods - Ozyilmaz, L; Yildirim, T (NANYANG TECHNOLOGICAL UNIV, 2002)
Proper interpretation of the thyroid gland functional data is an important issue on the diagnosis of thyroid disease. The primary role of the thyroid gland is to help regulation of the body's metabolism. Thyroid hormone produced by the thyroid gland provides this. Production of too little thyroid hormone (hypo-thyroidism) or production of too much thyroid hormone (hyper-thyroidism) definites the type of thyroid disease. In this work, various neural network methods have been used to help diagnosis of thyroid disease.
Keywords: Computer Science; Engineering; Imaging Science & Photographic Technology